Tafsir Nusantara: (Kajian Deskriptif Tafsir Indonesia Era Kontemporer) - Siti Fahimah (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2019)
The treasure of the development of interpretations in the archipelago, especially in Indonesia, can be seen from four aspects, namely the activities of recitation, writing, the development of religion, and the existence of institutions. Of the four conditions, various works emerge from the Koran to answer the problems of the Ummah which in its development the work is called interpretive work, because the Qur'an will always speak if it is always approached with diverse models and characteristics, the works of which are As a response to the diverse problems of the Ummah. The 14 works outlined in this paper have an average local interpretation tendency and to answer the problems that occur, but the description used is a brief description so that more research is needed, not only that the product of interpretation will not stop because the problems of the people will always develop , so it is necessary to find an official benchmark, namely the Qur'anic approach that is Indonesian-minded.